Examining pacing profiles in elite female road cyclists using exposure variation analysis - Abbiss, C. R.; Straker, L.; Quod, M. J.; Martin, D. T.; Laursen, P. B. (British Journal of Sports Medicine, 2010)
Objective: In this study, the amplitude and time distribution of power output in a variety of competitive cycling events through the use of a new mathematical analysis was examined: exposure variation analysis (EVA).